2012
DOI: 10.1177/1098612x12439269
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline silver dressing and subatmospheric pressure therapy following neoadjuvant radiation therapy and surgical excision of a feline injection site sarcoma

Abstract: This is the first clinical report of use of a combination of nanocrystalline silver and subatmospheric pressure therapy to treat a resistant wound infection, following tumour removal and radiation therapy, in a difficult-to-manage surgical site in a cat. Practical relevance The therapy was well tolerated and the authors suggest it is a valid treatment protocol for management of non-healing or infected wounds in the cat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Numerous publications have reported the beneficial effect of NPWT on the healing of complicated wounds in humans and animals, 1-20 but information regarding cats was limited to a number of case reports and a case study. 17,19,[28][29][30] Here, we demonstrated faster wound closure in cats undergoing NPWT compared with foamtreated animals.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous publications have reported the beneficial effect of NPWT on the healing of complicated wounds in humans and animals, 1-20 but information regarding cats was limited to a number of case reports and a case study. 17,19,[28][29][30] Here, we demonstrated faster wound closure in cats undergoing NPWT compared with foamtreated animals.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the same authors further demonstrated that nanosilver, as mycoad, can be useful in reducing the adverse effects of aflatoxin on blood parameters in chickens that are affected with aflatoxicosis [ 124 ]. The combination of nanocrystalline silver and subatmospheric pressure therapy shows significant effect in cat after following tumour removal and radiation therapy [ 125 ].…”
Section: Types Of Various Nanomaterials Used In Veterinary Medicinmentioning
confidence: 99%
“…Advances in biotechnology have enabled incorporation of ionisable silver into fabrics for clinical use to reduce the risk of nosocomial infections and for personal hygiene. 54 Although veterinary use of silver has not yet taken off, in 2012, Woods et al 57 reported the use of a combination of nanocrystalline silver dressing and subatmospheric pressure therapy to treat a resistant wound infection, following tumour removal and radiation therapy, in a difficult-to-manage surgical site in a cat.…”
Section: Essential Oilsmentioning
confidence: 99%